2017
DOI: 10.1002/2017jb014384
|View full text |Cite
|
Sign up to set email alerts
|

Field characterization of elastic properties across a fault zone reactivated by fluid injection

Abstract: We studied the elastic properties of a fault zone intersecting the Opalinus Clay formation at 300 m depth in the Mont Terri Underground Research Laboratory (Switzerland). Four controlled water injection experiments were performed in borehole straddle intervals set at successive locations across the fault zone. A three‐component displacement sensor, which allowed capturing the borehole wall movements during injection, was used to estimate the elastic properties of representative locations across the fault zone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Stresses following the lithostatic gradients are applied on all the boundaries, and permeable flow boundaries are imposed. A strike‐slip stress regime is applied to simulate displacements having the same direction as those monitored during the first rupture (Ev.1) with σ 1 = 9.4 MPa oriented N125°, σ 2 = 6.0 MPa vertical, and σ 3 = 4.7 MPa oriented N035° (Jeanne et al, ). The paleostress regime that generated the Main Fault is not accurately known, but the strike‐slip regime adopted here appears to be relatively consistent with paleostress estimations from fault planes striations (Nussbaum et al, ).…”
Section: Numerical Simulation Of Srt1mentioning
confidence: 99%
See 1 more Smart Citation
“…Stresses following the lithostatic gradients are applied on all the boundaries, and permeable flow boundaries are imposed. A strike‐slip stress regime is applied to simulate displacements having the same direction as those monitored during the first rupture (Ev.1) with σ 1 = 9.4 MPa oriented N125°, σ 2 = 6.0 MPa vertical, and σ 3 = 4.7 MPa oriented N035° (Jeanne et al, ). The paleostress regime that generated the Main Fault is not accurately known, but the strike‐slip regime adopted here appears to be relatively consistent with paleostress estimations from fault planes striations (Nussbaum et al, ).…”
Section: Numerical Simulation Of Srt1mentioning
confidence: 99%
“…The best fit, chosen by eye, is found with an initial permeability of 6 × 10 −17 m 2 and a Young's modulus of 1.0 GPa for the reactivated fault. A permeability of 10 −17 m 2 and a Young's modulus of 0.4 GPa and 1.4 GPa normal and parallel to the laminar structure of the claystone for the surrounding rock mass are used for the rock mass (a sensitivity analysis to these mechanical properties is shown in Jeanne et al, ). During injection, the fracture permeability evolves due to changes in effective stress.…”
Section: Numerical Simulation Of Srt1mentioning
confidence: 99%
“…characterizes the initial reversible expansion of the injection chamber, which is preferentially oriented almost perpendicular to the N50°35-to-45°dipping fault family affecting the chamber. Jeanne et al (2017) showed that this u 1 ! orientation and magnitude can be explained by the rock elastic modulus magnitude, which is 10 times lower perpendicular to existing fault planes than parallel to existing fault planes.…”
Section: Three-dimensional Displacement Evolution 421 Rupture Initmentioning
confidence: 95%
“…The relation between the compliance of the probe and the elastic response of the borehole wall has been studied extensively through laboratory tests and fully coupled hydromechanical modeling using the TOUGH-FLAC simulator (Jeanne et al, 2017). It was shown that the device is~10 times more compliant than the rock, and that the orientation and magnitude of displacements below the stimulation pressure strongly depends on the elastic anisotropy of the rock.…”
Section: 1029/2019jb017781mentioning
confidence: 99%
“…Drillcores from exhumed faults and deep boreholes provide some constraints on the permeability of fault zone materials, indicating that damage zones are regions of enhanced permeability where most flow, if not all, is concentrated (Brace, , ; Evans & Goddard, ). Few studies have been designed, however, to characterize the internal flow structure of damage zones due to the difficulty of accessing and hydraulically testing faults at depth, except in sedimentary basins where a growing number of underground experiments has been conducted recently (Cappa et al, ; Jeanne et al, , ). In deep crustal fault zones, much of our knowledge on fault‐controlled flow processes comes from indirect observations, such as seismicity (Jansen et al, ), which informs on fluid migration at the hectometer to km‐scale but generally lacks the spatial resolution to track flow at the scale of discrete subsidiary fracture systems.…”
Section: Introductionmentioning
confidence: 99%